Electron tomographic analysis of post-meiotic cytokinesis during pollen development in Arabidopsis thaliana - Otegui, Marisa Silvina (2004)
The mechanism of cell wall formation after male meiosis was studied in microsporocytes of Arabidopsis thaliana (L.) Heynh. by means of thin-section and immuno-electron microscopy and dual-axis electron tomography of high-pressure-frozen/freeze-substituted cells. The cellularization of four-nucleate microsporocytes involves a novel type of cell plate, called a post-meiotic-type cell plate. As in the syncytial endosperm, the microsporocyte cell plates assemble in association with mini-phragmoplasts. However, in contrast to the endosperm cell plates, post-meiotic type cell plates arise simultaneously across the entire division plane. Vesicles are transported along mini-phragmoplast microtubules by putative kinesin proteins and, prior to fusion, they become connected together by 24-nm-long linkers that resemble exocyst complexes. These vesicles fuse with each other to form wide tubules and wide tubular networks. In contrast to endosperm cell plates, the wide tubular networks in microsporocytes completely lack callose and do not appear to be constricted by dynamin rings. The most peripheral wide tubular networks begin to fuse with the plasma membrane before the more central cell plate assembly sites become integrated into a coherent cell plate. Fusion with the parental plasma membrane triggers callose synthesis and the wide tubular domains are converted into convoluted sheets. As the peripheral convoluted sheets accumulate callose and arabinogalactan proteins, they are converted into stub-like projections, which grow centripetally, i.e. toward the interior of the syncytium, fusing with the wide tubular networks already assembled in the division plane. We also demonstrate that the ribosome-excluding cell plate assembly matrix is delivered to the mini-phragmoplast with the first vesicles, and encompasses all the linked vesicles and intermediate stages in cell plate formation.